Model Konseptual Manajemen Konflik Dalam Organisasi - Dewie Tri Wijayati (BISMA (Bisnis dan Manajemen), 2018)
Organization is a place where different people with different opinion share the same goal. As a dynamic social environment, organization always change and influence by its internal and external of organization. Therefore, conflict will exist in organization as the result of differences, changes and oppositions in achieving goal. Conflict can be managed in such a way by using models of conflict management. The purpose of this paper is to explain about  how management should deal with conflict, and how to implement models of conflict management in overcoming conflicts